ANALISIS KESALAHAN BERBAHASA DALAM PIDATO MAHASISWA MPBI-UMS [Analysis of Language Errors in MPBI-UMS Student Speech] - Wara Angreni; Atiqa Sabardila (Kantor Bahasa Provinsi Maluku, 2021)
This study aims to describe the form of speech errors of the candidates for Regional Head of Kulon Progo Regency. The research method used is qualitative descriptions. The data source is the utterances of the student speech. The data collection techniques are listening and note-taking. The data analysis used referential matching techniques and articulatory phonetic equivalents, extension techniques in the distribution method and sign reading technology. The results of the study shows that there are language errors in the form of speech of the candidates for Regional Head of Kulon Progo Regency The five areas of error are (1) phonological errors including phonological change, phoneme formation and pronunciation, (2) morphological errors including prepositions, repetition, tone, and combination of meN- and -kan prefixes, (3) syntax errors including ambiguous sentences, redundant words, and unclear sentence types (4) sociolinguistic errors, including misuse of language coding in sentences, and (5) spelling errors in capital letters, and punctuation. Penelitian ini bertujuan mendeskripsikan bentuk kesalahan berbahasa pidato mahasiswa calon kepala daerah Kabupaten Kulon Progo. Metode penelitian menggunakan deskripsi kualitatif. Data penelitian berupa tuturan pidato mahasiswa. Teknik pengumpulan simak dan catat. Analisis data menggunakan teknik padan referensial dan padan fonetis artikulatoris, teknik perluasan dalam metode agih dan teknologi membaca tanda. Hasil penelitian terjadi kesalahan bahasa pada bentuk tuturan pidato mahasiswa calon kepala daerah Kabupaten Kulon Progo memiliki lima wilayah kesalahan yaitu (1) kesalahan fonologi termasuk kesalahan perubahan fonem, kesalahan pembentukan dan pengucapan fonem, (2) kesalahan morfologi meliputi preposisi, penulisan ulang, bentuk nada, dan tulis kombinasi prefiks meN- dan -kan, (3) kesalahan sintaks termasuk kalimat yang ambigu, rancu, kata-kata yang berlebihan, jenis kalimat yang tidak jelas (4) kesalahan sosiolinguistik, termasuk penyalahgunaan campur kode bahasa dalam kalimat, dan (5) kesalahan ejaan dalam huruf kapital, dan tanda baca.